A History of FDI in Hydropower Development in Nepal - Dhungel, Kamal Raj (Hydro Nepal: Journal of Water, Energy and Environment, 2016)
In Nepal, hydropower is an obvious target for foreign aid and foreign investment. To date, a number of notable hydropower projects were constructed through foreign aid and that history dates back to 1911, when the Britain supported the Pharping hydropower project near Kathmandu. Today, India, China, USA and Norway are investigating the prospects for Nepali hydropower development. This paper traces this history of Foreign Direct Investment (FDI) in Nepal. HYDRO Nepal Journal of Water Energy and Environment Volume- 18, 2016, January Page -22 to 24